Financial crisis and Romania’s economy - NĂFTĂNĂILĂ, Cristina Alina (Annals of Spiru Haret University. Economic Series, 2010)
The effects of the international financial crisis also have spread on the Romanian economy. In terms of the direct impact, the banking system was less affected by not being exposed to the toxic assets, and because of prudential and administrative measures adopted over the time by the National Bank of Romania. Indirectly, the international financial crisis is expanding on the Romanian economy on the multiple channels. The evolution of the financial crisis will lead economies into a deflationary spiral in the next year or even a longer lasting, as deficit reduction efforts will take large, and probably we shall assist an output of some euro area of weaker states.